Effect of pre-rolling temperature on the interfacial properties and formability of steel-steel bilayer sheet in Single Point Incremental Forming. (February 2021) - Hassan, Malik; Hussain, Ghulam; Ali, Aaqib; Ilyas, Muhammad; Malik, Sohail; Khan, Wasim A; Bal, Burak
The aim of this research was to investigate the effect of pre-rolling temperature on the interfacial properties in delamination modes 1 and 2; and formability in Single Point Incremental Forming (SPIF) of Steel-Steel (St-St) bilayer sheet prepared by roll bonding process. The roll bonding process was performed at three pre-rolling temperatures, 700°C, 800°C, and 950°C, with a constant thickness reduction ratio of 58%. The bond strength and critical strain energy release rate (CSERR) were measured to characterize the interface of St-St bilayer sheet. T-peel test for mode 1 and tensile shear test for mode 2 were conducted to determine the interfacial properties. The formability of St-St bilayer sheet in SPIF was measured in terms of maximum wall angle. The results showed that the increase in pre-rolling temperature from 700°C to 950°C enhanced the bond strength and CSERR, in both mode 1 and 2. The enhancement in bond strength with an increase in pre-rolling temperature was 149.5% and 203% in mode 1 and 2, respectively. However, the increase in CSERR in mode 1 and 2 was 115% and 367%, respectively. The formability of St-St bilayer sheet also showed an increasing trend with an increase in pre-rolling temperature. Moreover, a consistent relation between formability and interfacial parameters was observed. It was also found that to successively deform the bilayer sheet into the desired shape, it is necessary for the sheet to be heated above the critical temperature during fabrication to facilitate good bonding between two sheets.